(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Travel and Tours Management System is a comprehensive system that manages transactions related to travel and tours, creating itineraries, hiring staff, financial costs, and executive management. Human Resource II is in charge of dealing with problems or demands of people that happen inside an organization. They often oversee the hiring, firing, and onboarding of new workers, as well as the orientation process to assist employees, etc. When conflicts emerge among employees, HR professionals must complete records of every action taken against an employee for legal reasons. The Mblitz Travel and Tours management system is an innovative Human Resource System that uses facial recognition to track an employee’s daily time in and out. This method of verifying an individual’s identification using their face to prevent wrongdoing will not be deceived by the employee and will provide real-time visibility. Human Resources at Mbliz Travel & Tours requires extra protection to prevent information theft, so the Mblitz Travel and Tours Management System was developed to protect the data stored by HR. Lastly, our network design is an iterative process that includes topological design, network synthesis, and network realization, aimed at ensuring that a new telecommunications network or service meets the needs of the subscriber and operator. They suggest we be more precise because it is essential to know what tools we use. As a result of the discussion within our system, the project improved the HR process by implementing the advanced system of Human Resource II. Facial recognition has been added, automating the daily records of our employees. The travel and tours offer more convenience for securing individual identification with the use of real-time visibility, avoiding information theft, and iterative process meets the needs of our service. This is the strategy of being accountable for finishing travel and tours human resource II.